Compassion-Focused Therapy for Moral Injury Among Healthcare Professionals: A Burnout Prevention Counseling Model in Indonesian Public Hospitals - Septien Dwi Savandha (Asesment : Journal Of Counseling Guidance, 2024)
Background: Healthcare professionals in Indonesian public hospitals experience high rates of moral injury—psychological trauma resulting from ethical violations and systemic constraints—which precipitates chronic burnout and workforce attrition, yet culturally appropriate, evidence-based interventions remain scarce.Objective: This study aimed to develop and evaluate a compassion-focused therapy (CFT) model for preventing burnout by addressing moral injury among Indonesian healthcare professionals working in resource-constrained public hospital settings.Method: A convergent parallel mixed-methods design was employed involving 72 healthcare professionals (physicians and nurses) from three public hospitals in Java who participated in an eight-week CFT group intervention, with quantitative assessments measuring moral injury, burnout, and self-compassion at baseline, mid-intervention, and post-intervention, and qualitative semi-structured interviews exploring lived experiences and cultural appropriateness.Findings and Implications: Results demonstrated statistically significant reductions in moral injury severity (28.8%, d = 1.42), burnout across all dimensions (25.7%–36.8%, d = 1.00–1.39), and substantial increases in self-compassion (61.9%, d = 1.73), while qualitative findings revealed therapeutic mechanisms operating through shame reduction, values reconnection, compassionate courage development, and sustainable practice integration within Indonesian cultural contexts.Conclusion: The study establishes compassion-focused therapy as an effective, culturally resonant intervention for preventing healthcare workforce burnout through addressing moral injury, offering evidence-based frameworks for individual healing and organizational support systems applicable to resource-constrained healthcare settings globally.